Is Sustainability Really Sustainable? A Critical Review - Grazia Massimino; Gaetano Sciuto (Buildings, 2025)
In recent years, the research and development of sustainable materials have seen a growing interest. The driving force behind this is environmental policies that aim towards a transition to a circular economy. There are numerous investigations into the potential use of waste and/or by-products in building materials and components. Using such materials, called “secondary raw materials”, is to be favored due to their low environmental impact. Although research is numerous, most studies are limited to a purely performance assessment. There are still a few studies that also address environmental (or sometimes economic) aspects. Lacking such considerations, is it possible to say that the industrial product of research is truly sustainable? Is it enough to use secondary raw materials to define a product with a low environmental impact? By critically reviewing publications on this topic, this paper aims to highlight possible new developments for future research. Including environmental assessments among the criteria for evaluating the impact of research would provide a vision that is not limited only to the performance profile but can capture aspects that are currently underestimated. Overcoming this limitation would make it possible to obtain products capable of responding to the demands of sustainability regulations, avoiding the strategy of greenwashing.